Effectiveness and Predictors of Continuation of Paliperidone Palmitate Long-Acting Injection Treatment. Issue 5 (October 2015) - Whale, Richard; Pereira, Marco; Cuthbert, Sharon; Fialho, Renata
<x xml:space="preserve">Abstract</x> Abstract Antipsychotic long-acting injectable (LAI) medication has an important place as a treatment option in schizophrenia with evolving evidence to support clinical benefit over oral medication. Paliperidone palmitate is recently licensed as an LAI. We studied a naturalistic cohort of all identifiable patients who initiated paliperidone LAI in a specific United Kingdom region (Sussex) from first availability up to January 2013 (n = 179). Favorably, 60% of the cohort continued paliperidone LAI beyond 12 months from initiation. Schizophrenia diagnosis was significantly associated with 12-month continuation on univariate analysis (65% continuation rate at 12 months in this diagnostic subgroup). No baseline variables were identified as independently associated with 12-month continuation. However, fewer inpatient days after initiation (odds ratio [OR], 1.01; 95% confidence interval [CI], 1.003–1.011; P = 0.002), dose adjustment up or down (OR, 3.46; 95% CI, 1.26–9.51; P = 0.016), and a higher maintenance dose (OR, 8.31; 95% CI, 1.84–37.51; P = 0.006) during treatment course were all independently associated with continuation on multivariate analysis. Our findings support the importance of a collaborative approach with the LAI recipient in treatment decision making to enhance treatment effectiveness.